2000
DOI: 10.1007/pl00005841
|View full text |Cite
|
Sign up to set email alerts
|

Ossification Centers of Human Femur

Abstract: The purpose of the present work was to investigate the appearance of ossification centers in human femur by Dual-energy X-ray Absorptiometry (DXA), comparing densitometric data with morphogenetic events. Posteroanterior scans were performed on 31 dried femora (from 11.5 weeks of conceptual age to 1 year of postnatal life) by a Hologic QDR 1000 X-ray densitometer with Ultra-Hi-Resolution software. The results were expressed as bone mineral content (BMC, g) and bone mineral density (BMD, g/cm2). The analyses wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 15 publications
(19 reference statements)
0
3
0
Order By: Relevance
“…Ossification of the distal femoral end begins between weeks 23 and 40 of gestation [ 3 ]. However, these findings have been queried by Panattoni et al [ 15 ], who observed the onset of ossification in the trochanters during the intrauterine growth. Therefore, these authors hypothesized that neither extended posture nor ambulation affect, as it had previously been thought, the initiation of the development of the trochanteric ossification centers despite fetal movements can stimulate such ossification.…”
Section: Discussionmentioning
confidence: 99%
“…Ossification of the distal femoral end begins between weeks 23 and 40 of gestation [ 3 ]. However, these findings have been queried by Panattoni et al [ 15 ], who observed the onset of ossification in the trochanters during the intrauterine growth. Therefore, these authors hypothesized that neither extended posture nor ambulation affect, as it had previously been thought, the initiation of the development of the trochanteric ossification centers despite fetal movements can stimulate such ossification.…”
Section: Discussionmentioning
confidence: 99%
“…A primitive cartilage model of the appendicular bone is developed during fetal morphogenesis. [1][2][3][4] Invasion of blood vessels at the mid-diaphysis represents the first hint of bone formation in a continuing process of the formation of the primary ossification center. 4,5 In different mammalian species, the entire epiphysis of either the proximal or distal condyle is usually cartilaginous shortly before or after birth.…”
Section: Introductionmentioning
confidence: 99%
“…Once the epiphyseal plate fully ossifies, the bone can no longer grow in length. In mice, secondary ossification centers do not appear until after birth (Patton & Kaufman, 1995), but in humans some secondary centers can be detected prenatally (Panattoni, D'Amelio, Di Stefano, & Isaia, 2000).…”
Section: Somatic Developmental Effects Of Cannabis Smoke or ‐Thc In A...mentioning
confidence: 99%